ANALISIS FAKTOR - FAKTOR PEMANFAATAN SOFTWARE AKUNTANSI TERHADAP KINERJA PELAKU UMKM KECAMATAN MEDAN KOTA - Rahmawaty Hasibuan; Martalina Situmorang; Chris Dayanti Br. Ginting (Universitas Pahlawan Tuanku Tambusai, 2022)
The population in this study are owners or employees of Small and Medium Enterprises (SMEs) in Kec. Medan City which is registered with the Medan City Cooperative and UMKM Office. The analysis shows that the use of accounting software, trust and ease of use of accounting software has a positive and significant relationship to the performance of MSMEs in Kec. City Field. But partially it has an effect, only the ease of using accounting software has a positive and significant effect on individual performance, while the use of accounting software and trust has no relationship to the performance of MSME actors. The conclusion of this study is the use of accounting software, trust and ease of use of accounting software has a positive and significant relationship to performance. Keywords: Utilization, Trust, Convenience, Software, MSME Performance